Modern Historicism: the Universal History of E. Toffler - B. G. Sokolov (Дискурс, 2022)
Introduction. The article proposed to the reader aims at fixing universal historicity in the reconstruction of history by one of the most sought-after and well-known American futurists, Alvin Toffler. An analysis of his concept from such a perspective allows us to identify in modern concepts and, accordingly, in postmodernity (post-industrial era) genetic links with the previous tradition associated with the industrial era, which allows us to explore modern cultural trends, which seems to be an extremely urgent task for humanitarian knowledge. Such an approach to the study of modern futurological concepts in general, and E. Toffler's futurology in particular, has not been applied, and therefore the author's approach has both extreme relevance and theoretical novelty.Methodology and sources. The obtained research results were based on a comparative and textual analysis of the texts of the American thinker (Toffler E. “The Third Wave”, “Shock of the Future”), as well as texts of authors who thematized the universal historical model of understanding the historical process (G. Hegel). In carrying out the genetic and comparative analysis of E. Toffler, the author uses the results of his own research on the genesis of the historical consciousness of the New European culture. The analysis of the texts of E. Toffler and post-industrial society was carried out using modern critical studies (E.I. Furs, K. Ratti, M. Claudel).Results and discussion. The model of universal history, which has its origin in the Sacred History of Christianity, has the following basic essential characteristics: 1) the presence of the figure of the so-called transcendental signified, i.e. the mental topos that controls the historical process (in Christian history, God is such, in Hegel's system – the dialectical unfolding of the concept, in Marxist philosophy – the struggle of productive forces and production relations; 2) the understanding of the historical process as totality; 3) the presence of a common telos of historical development; 4) a special status of a real actor of a historical event (disenfranchised, “puppet”); 5) a universal homogeneous environment for the unfolding of the historical process; 6) the stages of the historical process.The comparative analysis of the reconstruction of Alvin Toffler's views and the main characteristics of universal history, as well as the use of critical sources on the subject of the article, shows that for all the essential points listed above, history, as it is built by the American futurist, is undoubtedly a universal history.Conclusion. The use of such an outdated point of view of modern mentality, the vision of the historical process actually fulfills two important tasks, which the author of the article focuses on. 1. The opportunity to see and evaluate rapid changes from the point of view of the future (as stated by Toffler himself). 2. Infection of the future with the models and approaches of the previous industrial society, which clarifies the processes of building the modern cultural situation, allowing you to understand current development trends.